A study on factor that affecting job satisfaction among employees in Kuala Terengganu / Norhaizal Mahussain - Mahussain, Norhaizal (Bachelor of Science (Hons.) Statistics, 2015)
The purpose of this study was to determine the factor that affecting level of job satisfaction among employees in Kuala Terengganu. A random sample of 103 respondent who makes an complaint from 140 population was selected as a statistical sample. Employing a descriptive survey method and data were collected through questionnaire. Mutiple regression analysis was used to investigate the significant different between factors (working environment, job security, salary and benefit) and to test the relationship between variable. The result from Independent T-test and ANOVA table shows that the employees were generally satisfy with theirs job. The factor ‘working environment’ mostly contributed to employee’s job satisfaction. The factors ‘working condition’, ‘job security’ and ‘salary and benefit’ explained 64.7% of variance among employees who makes an compalint regarding to their work. For demographic variable (age, level of education and working period) do not contrinuted to level of job satisfaction. These analysis were analyze by using SPSS 2.0 (Statistical packages for Social Software)